Analisis kadar vitamin C pada buah naga putih (Hylocereus undatus) dan buah naga merah (hylocereus polyrhizus) dengan perbandingan metode spektrofotometri uv dan titrasi iodimetri - Claudy Friesta Melanie; Gabena Indrayani Dalimunthe; Ridwanto; Fathur Rahman (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Dragon fruit is natural source of antioxidants. We can consume not only dragon fruit flesh, but the skin is also very beneficial for health, in reality it is only considered as waste that has not been used properly. This study aims to analyze the levels of vitamin C in white dragon fruit and red dragon fruit with a comparison of uv spectrophotometry and iodimetric titration methods. The stages of the research included extracting from dragon fruit, screening phytochemicals, testing levels of vitamin C using iodimetric titration, testing levels of vitamins using UV spectrophotometry. The results showed that red dragon fruit contains alkaloids, flavonoids, saponins, tannins, triterpenoids and glycosides, while white dragon fruit contains alkaloids, flavonoids, saponins and steroids. Determination of vitamin C levels by iodimetric titration method on red dragon fruit skin was 9.240 ± 3.029 mg, on red dragon fruit flesh was 11.587 ± 1.893 mg and vitamin C levels on white dragon fruit skin was 9.827 ± 3.933 mg, on white dragon fruit flesh was 13.347 ± 3.143 mg in 100 gram sample. While the spectrophotometric method obtained vitamin C levels in white dragon fruit flesh, namely 332.93 mg/100g, in red dragon fruit flesh, 24.99 mg/100g, while red dragon fruit skin, which was 16.59 mg/100g, in white dragon fruit skin, namely 10.47 mg/100g.